Meningkatkan Semangat Belajar Siswa Menggunakan Media Visual - Emanuel, Emanuel Faomasi Gowasa; Ratni, Okte Ratni Tuberta Memowua Gowasa (CV. SINAR HOWUHOWU, 2025)
This journal aims to understand the positive and negative impacts of visual media in students learning motivation. We know that at this time the enthusiasm for leraning of students is starting to decline,this isbecause the teaching methods commonly used by teacher/lecturers are very monotonous and boring so that students are now starting to get bored with the lessons delivered by their teachers/lectures. With the learning methods using visual media that has been applied by teachers, students interest in learning has now increased so that students are now actively learning using visual media and students now like to explore the knowledge they have just learned.